Structure of Fibers of Sickle Cell Hemoglobin - Edelstein, Stuart J. (1973)
Electron microscope studies have been conducted on individual fibers of human deoxyhemoglobin S (sickle cell hemoglobin). The fibers are obtained by injection of gelled samples into a large excess of glutaraldehyde, which quickly stabilizes the fibers by cross-linking. The fibers are negatively stained with phosphotungstic acid or shadowed with platinum-carbon. The fibers are approximately 200 Å in diameter, and display long and short helical striations with an opposite handedness. The long striations occur at an angle of about 15° from the fiber axis, and complete one turn around the helix at a distance of about 2 × 10(3) Å along the fiber axis. The short striations occur at an angle of about 80° from the fiber axis, with a spacing of about 65 Å, and complete one turn around the helix at a distance along the fiber axis of about 130 Å. The structure of the fiber appears to be a sextuple helix in terms of the long striations, and a double helix in terms of the short striations. The shadowed samples are consistent with a left-handed screw sense for the short striations, thus implying a right-handed sense for the long striations. A structural model incorporating these features is compatible with the atomic structure of hemoglobin, with individual molecules oriented with their dyad axis of symmetry perpendicular to the fiber axis and their α(1)-β(1) pseudo-dyad axis roughly parallel to the fiber axis. This orientation places the two β-6 regions of each molecule (sites of the sickle cell mutation) in contact with the β-6 regions of the molecules above and below along the long striations. Both the long and short striations are accounted for by individual hemoglobin molecules arranged in double helical arrays with 6.4 molecules per turn in each array.